Characterization of extremely halophilic Archaea isolated from the Ayvalik Saltern, Turkey - BİRBİR, MERAL (SPRINGER, 2004)
Seven extremely halophilic strains were isolated from the Ayvalik Saltern in the north-eastern part of Turkey. Chemical analyses of the brine and salt samples were performed to measure their salt content, hardness and pH. Isolated strains were tested for their antibiotic sensitivities; cell and colony morphologies; hydrolysis of casein, starch, gelatin, Tween 20 and Tween 80; and oxidase and catalase activity. All strains were found to belong to the domain Archaea. Characterization of polar lipids by thin layer chromatography indicated that all isolates contained phytanyl diether derivatives of phosphatidylglycerol (PG), the methyl ester of phosphatidyl glycerophosphate (PGP-Me), and phosphatidylglycerosulphate (PGS). Four isolates had triglycosyl diether (TGD-2) as glycolipid, and the other three contained a sulphated diglycosyl diether instead. All isolates were examined for the presence of plasmids by agarose gel electrophoresis. Four strains were found to harbour plasmids ranging in size from 13.8 to 15.3 kbp. Correlation between the protein profiles in SDS-PAGE and the phenotypic properties of the strains was poor. The data presented here provide the first published account of the microbiota of the Ayvalik saltern, which provides a large part of the salt produced in Turkey.
Keywords: Archaea; exoenzymes; extremely halophilic Archaea; salterns; Turkey; POLAR LIPID-COMPOSITION; SP NOV.; GEN-NOV; HALOBACTERIA; PROFILES; TAXONOMY; ECOLOGY; SQUARE